Authority between Text and Context: Sources, Methods, and Interpretation Patterns of the Companions of the Khulafāu al-Rāsyidīn on Casuistic Issues - Shovy, Abd.; Nabilah, Is‘ad Durrotun; Chasanah, Mas Nadia; Irhamni, Muhammad Adam Ali Fikar; Maula, Anjani I‘anatul; Najakhah, Vina Umdatun (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
The rationale for this research stems from the polarization of two groups: the Islamic Orthodox group and the group of inclusive reform thinkers. The problems that occurred since the time of the prophet and Khulafau al-Rasyidin's companions are very likely different from today's more complex times. Therefore, the researcher wants to re-read the intellectual struggle of the Companions in interpreting the Qur'an on casuistic issues at that time. Starting from the source, method, style of interpretation, and the struggle between text and context. The research method of this article uses the library research method, in which all data is taken from written materials that are directly related to and correlate considerably with the topic under study. One fundamental principle is that all the companions agreed that the preeminent source is the Qur'an and Hadith. It follows that the purpose of the Shari'ah that God intends is the purpose for which it contains elements of human benefit. The preservation of religion, soul, mind, lineage, and property. Known as Maqasidhu al-Sharia.